The Ossuary of 'Miriam Daughter of Yeshua Son of Caiaphas, Priests [of] Maʿaziah from Beth ʾImri' - Zissu, Boaz; Goren, Yuval (2011)
The Israel Antiquities Authority recently acquired a decorated limestone ossuary purportedly from a burial cave in the area of the ʾElah Valley. An inscription, incised on the front of the ossuary, reads: מרים ברת ישוצ בר קיפא כהנמ מצויה מבית אמרי ('Miriam daughter of Yeshua son of Caiaphas, priests of Maʿaziah from Beth ʾImri'). The script is formal, of the style common in ossuary inscriptions in Jerusalem of the late Second Temple period. On palaeographic grounds, it should be dated to the late first century BCE or to the first century CE. The prime importance of the inscription lies in the reference to the ancestry of the deceased — the well-known family of Caiaphas priests active in the first century CE. The article discusses whether Beth ʾImri is a toponym or the name of a priestly family that settled there. The relatively careless execution of the design suggests that this ossuary was produced in a Judaean workshop and can be dated to 70–135 CE, a dating supported by two pottery oil-lamps apparently found in the burial cave. Since the ossuary in question was not found in a controlled excavation and due to its importance, it was subjected to scientific analyses in order to address the question of authenticity. The examinations focused on the patina coating the stone surface, with emphasis on the inscribed area. The patination of the stone, in and around the inscription, indicates a complex process that occurred over a prolonged sequence of time, which is extremely difficult, if not impossible, to replicate in laboratory conditions. It may be concluded, therefore, that the patina and the inscription should be considered authentic beyond any reasonable doubt.